Anatomical study of the obturator internus, gemelli and quadratus femoris muscles with special reference to their innervation - Aung, Htar Htar; Sakamoto, Hirokazu; Akita, Keiichi; Sato, Tatsuo (Wiley-Liss, INC., 2001)
The manner of innervation of the obturator internus, superior and inferior gemelli, and the quadratus femoris in humans (101 pelvic halves) and in rheus monkeys (Macaca mulatta: 8 pelvic halves) were investigated. In most specimens, the inferior gemellus originated from the lateral surface of the ischial tuberosity and also from the medial surface (intrapelvic origin) just beneath the obturator internus and was covered by the falciform process of the sacrotuberous ligament. The superior gemellus was frequently innervated by the nerve to the obturator internus and the nerve to the quadratus femoris (60.4%) qnd the inferior gemellus was innervated by the obturator internus nerve in two specimens. The quadratus femoris nerve originated from more cranial segments than the obturator internus nerve, however these nerves had various communication patterns inside and outside the muscles. According to the intramuscular nerve distribution, in some specimens the branches to the superior gemellus from the quadratus femoris nerve extended to the inferior gemellus, and the branches to the inferior gemellus were distributed to the obturator internus. The present findings revealed that the positional relationships among the branches to the obturator internus and gemelli muscles are relatively constant, although the branching patterns and innervation patterns were varied. The various patterns and routes are considered to reflect the variability of the differentiation patterns of the anlage of the muscles. A possible schematic model of the positional relationships between the muscles and the nerves is proposed.